TIMP2 and IGFBP-7 as Biomarkers For The Diagnosis of Acute Kidney Injury (AKI) in Post-operative Patients: An Evidence-Based Case Report - Igor Ian Wiguna; Gde Ngurah Irfan Bhaskara; Mutiara Reka Ananda Putri; Priscilla Ardianto; Widi Atmoko (Acta Medica Indonesiana, 2023)
Background: Acute kidney injury (AKI) is defined as a sudden reduction in kidney function which commonly occurs as a complication of major surgeries. It is traditionally diagnosed using serum creatinine elevation. AKI has relatively slow kinetics that makes it unable to diagnose at an earlier more reversible stage. Furthermore, previous research has shown that TIMP-2 and IGFBP7 were urinary biomarkers to use as a diagnostic tool for AKI. We aimed to compare the accuracy of TIMP2 and IGFBP-7 to the gold standard (serum creatinine) in diagnosing AKI in postoperative patients. Methods: A thorough search was performed using a search strategy on EMBASE, PubMed, and Medline (Ovid) using keywords according to the objective. The collected articles were critically appraised using CEEBM critical appraisal tool. Results: 5 studies that fulfilled the inclusion criteria were selected and evaluated. They all stated that the use of TIMP2 and IGFBP7 could not detect AKI better than the gold standard as shown in the sensitivity and specificity of the biomarkers. Furthermore, the examination of AKI using both biomarkers showed a sensitivity of 60-100% and specificity of 58-91%. Conclusion: TIMP2 and IGFBP7 are promising diagnostic tools for AKI. However, due to the wide variation in results amongst the different studies, further research is required to ensure the credibility of this result.